2008
DOI: 10.3177/jnsv.54.460
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Endotoxin on Plasma Free Amino Acid Concentrations in Rats

Abstract: SummaryWe examined the effects of lipopolysaccharide (LPS) injection on body temperature and plasma free amino acid concentrations in rats. A catheter was placed in the jugular vein of the rats in order to draw blood from and to inject LPS into awake animals. On the day of the experiment, body temperature was recorded during the experiment (330 min) and blood was drawn before and at several time points after injection of LPS (10 g/kg body weight). Body temperature in LPS-treated rats began to rise ~30 min afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Plasma Asn concentrations decreased in LPSchallenged steers, which is a consistent response among studies with cattle (Waggoner et al, 2009a,b;Carter et al, 2010) and other species (Asai et al, 2008). Both Asn and Gln are activators of ornithine decarboxylase for polyamine synthesis in proliferating cells (Ray and Johnson, 2014), and Asn reduces intestinal damage of pigs after LPS exposure (Chen et al, 2016).…”
Section: Endotoxin Challengesupporting
confidence: 63%
“…Plasma Asn concentrations decreased in LPSchallenged steers, which is a consistent response among studies with cattle (Waggoner et al, 2009a,b;Carter et al, 2010) and other species (Asai et al, 2008). Both Asn and Gln are activators of ornithine decarboxylase for polyamine synthesis in proliferating cells (Ray and Johnson, 2014), and Asn reduces intestinal damage of pigs after LPS exposure (Chen et al, 2016).…”
Section: Endotoxin Challengesupporting
confidence: 63%
“…In the present study, the amino acids that inhibited KYN uptake are consistent with substrate amino acids of LAT 1 rather than LAT 2, suggesting a critical role of LAT 1 in KYN uptake in the brain. K m values of LAT 1 for leucine, isoleucine, methionine, phenylalanine, and tyrosine are 15–30 μmol/L, around physiological concentrations (Asai et al 2008 ), indicating higher affinity than for KYN (Yanagida et al 2001 ). The other amino acids (glutamine and aspartate) have low affinity for LAT 1 ( K m = 1.5–2 mmol/L), and are not substrates of LAT nor affect tissue KYN concentration.…”
Section: Discussionmentioning
confidence: 99%
“…We precisely investigated the effect of 10 amino acids on KYNA production and KYN uptake at 3 μmol/L–3 mmol/L. The physiological concentrations of leucine, isoleucine, phenylalanine, methionine, tyrosine, alanine, aspartate, cysteine, glutamine, and glutamate are approximately 150, 90, 60, 50, 70, 400, 10, 10, 700, and 80 μmol/L in rat plasma, respectively (Asai et al 2008 ). Interestingly, all 10 amino acids partially inhibited KYNA production at physiological concentrations, with IC 50 values of most amino acids for KYNA production or KYN uptake around physiological levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to demonstrate that, 3 h after an LPS injection, there is an increased relative isotopic abundance in plasma amino acids (alanine, proline and threonine) relative to their levels prior to LPS injection and relative to the levels of saline‐injected controls. Asai et al demonstrated that plasma concentrations of individual amino acids quickly decrease then increase in the first 6 h of the response to endotoxin with a pivotal point at 3 h after injection in rats 29. Phenotypic variation due to the LPS stimulus and the timing of the 3‐h sample, a potential inflection point in plasma amino acid concentration, may have led to a high degree of variability in the observed shift in amino acid isotope abundance.…”
Section: Discussionmentioning
confidence: 99%